METHODOLOGICAL PRINCIPLES OF INDUSTRIAL ENTERPRISE DEVELOPMENT MANAGEMENT - Karine A. Barmuta; Besarion C. Meskhi (Advanced Engineering Research)
To lend logical completeness, effectiveness and structuredness to the industrial enterprise developm ent manag ement process, it is necessary to follow a number of methodological principles of the enterpris e development ma nagement. The conceptual methodological principles on the formation of the enterprise development man agement system aimed at the effectivization of the industrial engineering operation and quality are offered.